(untitled) (World Science, 2021)
The analysis of the causes of postoperative complications was carried out, as well as of the failures and errors or the same omissions in postoperative management. The total number of cases was 177 (5%) among more than 3500 patients, being operated on various clinical and anatomical forms of craniocerebral trauma. In 63.8% (in 113 patients), worsening of condition was associated with the postoperative hemorrhage, which in 54% of cases was shell- recurrent. In 36.6% of observations (in 64 patients), deteriorated states of the brain swelling or edema were associated with an increase of cerebral edema. The main causes of the postoperative volume hemorrhages were the inadequacy of homeostasis and fluctuations in blood pressure during the first hours and days after surgery, with a tendency of significant increase of that latter. Diagnostic errors were the result of underestimation or incorrect evaluation of neurological symptoms and clinical signs of repeated volumetric hemorrhages. Late diagnosis of postoperative complications resulted in a lethal outcome in 79 (44.6%) cases among 177 patients with the complications in the postoperative process. Neurological and clinical signs and their combinations characteristic for postoperative volumetric hemorrhages are given in the article, as well as are offered the ways of their prevention.